Heavy metal bioaccumulation in sediment, common reed, algae, and blood worm from the Shoor river, Iran. (March 2016) - Hamidian, Amir Hossein; Zareh, Maryam; Poorbagher, Hadi; Vaziri, Leila; Ashrafi, Sohrab
Concentrations of 11 metals (cadmium, zinc, copper (Cu), vanadium (V), lead, magnesium (Mg), manganese, aluminum, iron (Fe), chromium (Cr), and nickel), and one metalloid (arsenic (As)) were measured in sediment, common reed ( Phragmites australis), algae ( Spirogyra sp.), and blood worm ( Chironomus sp.) tissues of samples collected from the Shoor river. Samples were dried, acid digested, and the concentrations of metals were measured using inductively coupled plasma–optical emission spectrometer. A higher concentration of heavy metals was accumulated in Spirogyra and Chironomids than sediment and common reed. The highest rate of accumulation was found for Mg, V, Fe, As, Cu, and Cr. Spirogyra and Chironomids are capable of accumulating and thereby removing metals from polluted water bodies and are suitable for biomonitoring purposes.